Analisis administrativo-financiero en la Cooperativa de Ahorro y Crédito San Sebastián de la ciudad de Loja, períodos:2010-2012 - Loján Quizhpe, MIriam Ivanova (2016)
The titled thesis work: ADMINISTRATIVE ANALYSIS - FINANCIAL IN THE COOPERATIVE OF SAVING AND CREDIT SAN SEBASTIAN OF THE CITY OF LOJA, PERIODS: 2010 - 2012, the same one that developed it based on the General Target: To realize the administrative - financial analysis that allows to know the operation capacity of the Cooperative of Saving and Credit San Sebastian, periods 2010-2012, with the purpose that his managers take the best decisions. For the suitable process it was necessary to take into consideration the fulfillment of each of the raised targets, being the first specific target “to analyze the management in the administrative ambience of the Cooperative” to fulfill the same one was precise the application of surveys and interviews to the personnel of the cooperative to know the Labor Satisfaction and Performance of the Human Talent. The second specific target establishes “to apply the vertical and horizontal analysis in order to know the structure and changes” by means of the Financial conditions of the Cooperative in the years 2010-2012”. The third specific target is “to evaluate the administrative - financial management across the application of the method Minimal Threshold of Financial 6 Management of Integral Evaluation of the Popular and United Financial Sector” with the indicators application the financiers who are divided in Solvency, Structure of Portfolio, Slowness, Liquidity and Sostenibility. The fourth specific target establishes “to propose improvement alternatives to the administrative - financial management”, like the socialization of the results to motivate collective commitments gathering the fortitude of the group of work in order to which this one is more competitive on the market that is unrolled and to increase the adherence d new associates minimizing the desertion of the same ones. To fulfill all the raised targets there was used the scientific method that allowed the data collection using the concepts, judgments and logical reasonings as for the administrative - financial analysis, also other methods were used like deductive, inductive, analytical, synthetic, statistical and mathematical, also there were used different skills as the direct observation, made out survey and bibliographical compilation. Finally it presents the conclusions to itself, in the administrative ambience most of the personnel are in good work environment and the same ones expire with the requirements that the cooperative demands this way optimizing resources and between the recommendations it stands out in the administrative ambience that is, that every employee possesses an evidences folder to know the evolution of the personnel and in financial ambience to use financial indicators according to the size of the cooperative to know the current situation of the Cooperative, as well as of a financial structure that should assure the financial development and the conception of major benefits that should motivate his associates and clients to keep on being entrusted in the same one.